(3GJLGgGJ MOjKI aj GdJOQjHs - (3HdGd Nda(B, (3GdScGQfIs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2011)
(3eaghe h CgejI GdJOQjH h adSaI GdYedjI GdJOQjHjI , JMdjd h JMOjO GdGMJjGLGJ GdJOQjHjI , JUeje GdHQGeL GdJOQjHjI h GdWQb h GdCSGdjH GdJOQjHjI , GdhSGFd h GdeSGYOGJ GdJOQjHjI h Jbhje GdHQGeL GdJOQjHjI , GdMbGFH GdJOQjHjI , GOGQI GdYedjGJ h GdCfTWI GdJOQjHjI h Jchjf GdeOQH GdfGLMs
Keywords: (3EOGQI GdCaQGOs; (3GdJOQjHs; (3GdJOQjH GdEOGQjs